Penerapan Pendekatan Coperative Learning Tipe Think Pair Share (TPS) untuk Meningkatan Proses Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar - Andesna, Putri; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study attempts to improve student learning process  in integrated thematic learning through used the of cooperative learning approach type think pair share (TPS) to the fourth grade students ofi SD Negeri 09 Parak Gadang Kecamatan Padang Timur. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection.. This study was conducted at SD Negeri 09 Parak Gadang Kecamatan Padang Timur to 29 students. The results of speaking skill at the thinking stage of 57.8 (enought) to 57.8 ( Good). At the pair stage of  55.6  (enough) to 84,65  (Good). (3) The aspects of students of 53.3  (enaugh) to 81,4  ( Good). It can be concluded that the can improve the cooperative learning think pair share type (TPS)  integrated speaking skill in elementary schools.